Scaling up the use of low-emissions development (LED) research outputs in Vietnam: Co-design of LED research priorities, outputs, and impact pathways for emissions reduction from the livestock sector - Khatri-Chhetri, Arun; Anh, Le Hoang; Huong, Hoang Thi Thien; Huyen, Le Thi Thanh; Huong, Nguyen Thi Lien; Wollenberg, Eva Karoline (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Key messages – Using a rational formulation tool (PC Dairy Software) with locally available feeds can increase productivity and income of dairy farmers and reduce methane emissions. This requires building the capacity of policymakers, extension officers, dairy farmers, and feed industries to facilitate the use of the livestock PC Dairy Software and the national deed database. – Co-designing low-emissions development (LED) research priorities, outputs, and impact pathways with user input ensures relevant research and generates impact. This helps develop and refine research outputs, communication with stakeholders, and integration into LED policies and strategies. – Promoting improved feed by using the national feed database and PC Dairy Software can contribute to achieving Vietnam’s greenhouse gas (GHG) reduction targets set in the nationally determined contribution (NDC) and green growth strategy (GGS).